Tolosa-Hunt Syndrome – Case Report - Sandra Zečević Penić; Marijana Lisak; Tomislav Gregurić; Hrvoje Hećimović; Vanja Bašić Kes (Acta Clinica Croatica, 2017)
This case report presents a patient diagnosed with Tolosa-Hunt syndrome (THS) after an extensive neuro-diagnostic and neuroimaging evaluation. Diagnostic work-up included thorough physical and neurological examination, complete laboratory serum assessments, neuroendocrine and immunohistochemistry analysis, cerebrospinal fluid analysis, neurophysiology assessment, ophthalmologist examination and neuroimaging. Th e most important diagnostic tool in deriving the diagnosis of THS was neuroimaging evaluation that included baseline and follow-up cranial contrast enhanced magnetic resonance imaging (MRI). Baseline cranial contrast enhanced MRI detected a nonspecific inflammatory granulomatous lesion in the right cavernous sinus extending basally towards the right trigeminal cave (Meckel‘s cave) and anteriorly towards the apex of the right orbit. Systemic intravenous high-dose corticosteroid therapy was administered for 3 consecutive days and then tapered down to lower oral steroid doses. Following therapy, the patient experienced complete regression of symptoms. Follow-up cranial contrast enhanced MRI showed significant regression of inflammatory lesion in the area of right cavernous sinus, thus verifying the efficacy of the treatment applied. This paper shows that an extensive diagnostic schedule for THS must be conducted prior to therapeutic treatment, for the possibility of alternative diagnosis. Patients suspected of having THS require careful evaluation, appropriate treatment, and follow-up.